L’œuvre géographique récente de Jean Gottmann - Camu, Pierre (Cahiers de géographie du Québec, 1956)
Professor Jean Gottmann has written Jour books in the past six or seven years which constitute his main contribution to geography, especially in the field of political and economic geography.Some of his ideas are and will be discussed ; they certainly bring forward new approaches to old problems and new techniques to old methods. His four books are analyzed and reviewed together : l'Amérique (1949), A Geography of Europe (1950), la Politique des États et leur géographie (1952), Virginia at mid-century (7955).